1996
DOI: 10.1177/0044118x96028001004
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-Parent Attachment and Adolescents' Relations with their Peers

Abstract: We hypothesized that adolescents who reported secure attachments with their parents would display higher levels of interpersonal relational competence. Sixty-three 10th-grade pupils completed the Inventory of Parent Attachment and the Interpersonal Competence Questionnaire. Despite the fact that attachment is generally conceptualized as a unidimensional construct, we found little concordance between positive aspects of attachment (i.e., trust and communication) and alienation from parents. Although alienation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
1
28
0
2
Order By: Relevance
“…Freeman and Brown (2001) reported that among adolescents with insecure parental attachment, most selected a peer as their primary attachment figure, a finding replicated by other researchers (Hazan and Zeifman, 1994;Schneider and Younger, 1996). Crowell and colleagues (1999) reported correlations between parental attachment and peer attachment to be small (less than 0.35), suggesting that the two forms of attachment are separate constructs and occur within individuals in relatively independent levels.…”
Section: Parental Attachmentmentioning
confidence: 83%
See 1 more Smart Citation
“…Freeman and Brown (2001) reported that among adolescents with insecure parental attachment, most selected a peer as their primary attachment figure, a finding replicated by other researchers (Hazan and Zeifman, 1994;Schneider and Younger, 1996). Crowell and colleagues (1999) reported correlations between parental attachment and peer attachment to be small (less than 0.35), suggesting that the two forms of attachment are separate constructs and occur within individuals in relatively independent levels.…”
Section: Parental Attachmentmentioning
confidence: 83%
“…Several studies have suggested that in contrast to the early childhood occurrence of parents serving as children's primary (and dominant) attachment figure, specific aspects of attachment gradually shift to peers over the course of mid-childhood to late adolescence (Crowell and Waters, 1994;Fraley and Davis, 1997;Freeman and Brown, 2001; Furman and Wehner, 1997;Hazan and Shaver, 1987;Hazan and Zeifman, 1994;Schneider and Younger, 1996;Sroufe and Waters, 1977). Improved clarification of this maturational process of children's reorienting aspects of attachment from parents to peers could provide insight as to how attachment is associated with healthy and unhealthy emotional, behavioral, and relationship development.…”
Section: Peer Attachmentmentioning
confidence: 99%
“…Separations from a caregiver to whom the child is attached are considered detrimental to development, including problems with peer relationships, aggression, poor school performance, and self-esteem (Ainsworth & Witting, 1969;Marcus & Betzer;O'Koon, 1997;Schneider & Younger, 1996). The American Academy of Child and Adolescent Psychiatry (AACAP; 1997) guidelines for custody evaluation state that parent-child attachment should be assessed when determining child placement.…”
Section: Attachmentmentioning
confidence: 99%
“…Proponents of the deviance syndrome perspective argue that the same basic theoretical elements explain these various forms of deviant behavior (e.g., Deinbo et al, 1992;Gottfredson & Hirschi, 1990;Jessor et al, 1991). The theoretical elements examined represent an integration of social control (Durkheim [1897(Durkheim [ ] 1951Hirschi, 1969;Nye, 1958;Reckless, 1961) and attachment (Bowlby, 1969(Bowlby, , 1973(Bowlby, , 1980Schneider & Younger, 1996) theories. Both theories describe formation and maintenance of an cnduring emotional attachment between children and their parents or primary caretakers.…”
Section: Theoretical Framework For the Studymentioning
confidence: 99%